Involvement of Inflammasome Components in Kidney Disease - Ana Karina Aranda-Rivera; Anjali Srivastava; Alfredo Cruz-Gregorio; José Pedraza-Chaverri; Shrikant R. Mulay; Alexandra Scholze (Antioxidants, 2022)
Inflammasomes are multiprotein complexes with an important role in the innate immune response. Canonical activation of inflammasomes results in caspase-1 activation and maturation of cytokines interleukin-1β and -18. These cytokines can elicit their effects through receptor activation, both locally within a certain tissue and systemically. Animal models of kidney diseases have shown inflammasome involvement in inflammation, pyroptosis and fibrosis. In particular, the inflammasome component nucleotide-binding domain-like receptor family pyrin domain containing 3 (NLRP3) and related canonical mechanisms have been investigated. However, it has become increasingly clear that other inflammasome components are also of importance in kidney disease. Moreover, it is becoming obvious that the range of molecular interaction partners of inflammasome components in kidney diseases is wide. This review provides insights into these current areas of research, with special emphasis on the interaction of inflammasome components and redox signalling, endoplasmic reticulum stress, and mitochondrial function. We present our findings separately for acute kidney injury and chronic kidney disease. As we strictly divided the results into preclinical and clinical data, this review enables comparison of results from those complementary research specialities. However, it also reveals that knowledge gaps exist, especially in clinical acute kidney injury inflammasome research. Furthermore, patient comorbidities and treatments seem important drivers of inflammasome component alterations in human kidney disease.